Changes in surface water chemistry caused by natural forest dieback in an unmanaged mountain catchment - Kopáček, J; Fluksová, H; Hejzlar, J; Kaňa, J; Porcal, P; Turek, J (The Science of the total environment, 2017)
Ionic and nutrient compositions of throughfall, tributaries and lake outlet were analysed in the Plešné catchment-lake system (an unmanaged mountain forest in Central Europe) from 1997 to 2016. The aim was to evaluate changes in surface water chemistry after natural forest dieback. In the 2004-2008, 93% of the Norway spruce trees were killed by bark beetle outbreak, and all dead biomass remained in the catchment. Forest dieback changed the chemistry of all water fluxes, and the magnitude, timing, and duration of these changes differed for individual water constituents. The most pronounced decreases in throughfall concentrations occurred for K+, dissolved organic carbon (DOC), Ca2+ and Mg2+, i.e. elements mostly originating from canopy leaching, while concentrations of NH4+ and soluble reactive phosphorus (SRP) remained almost unaffected. In tributaries, the most rapid changes were increases in NO3-, K+, H+ and ionic aluminium (Ali) concentrations, while terrestrial export of DOC and P forms started more slowly. Immediately after the forest dieback, increase in NO3- concentrations was delayed by elevated DOC availability in soils. NO3- became the dominant anion, with maximum concentrations up to 346μeqL-1 within 5-7years after the bark beetle outbreak, and then started to decrease. Terrestrial exports of Ali, K+, H+, Mg2+, and Ca2+ accompanied NO3- leaching, but their trends differed due to their different sources. Elevated losses of SRP, DOC, and dissolved organic nitrogen continued until the end of the study. In the lake, microbial processes significantly decreased concentrations of NO3-, organic acid anions, H+ and Ali, and confounded the chemical trends observed in tributaries. Our results suggest that terrestrial losses of elements and the deterioration of waters after forest dieback are less pronounced in unmanaged than managed (clear-cut) catchments.
Keywords: Trees; Nitrogen; dusík; Forests; Bark beetle; lesy; stromy; Water Microbiology; Lakes; Europe; jezera; Carbon; Phosphorus; voda; Organic carbon; Base cations; Aluminium; mikrobiologie vody; Water; uhlík; Evropa